Compelling Comprehensible Input, Academic Language and School Libraries - Stephen Krashen; Janice Bland (CLELEjournal, 2014)
There is abundant research confirming that we pass through three stages on the path to full development of literacy, which includes the acquisition of academic language. The stages are: hearing stories, doing a great deal of self-selected reading, followed by reading for our own interest in our chosen specialization. At stages two and three, the reading is highly interesting or compelling to the reader. It is also specialized; there is no attempt to cover a wide variety. The research confirms that the library, in particular school library, makes a powerful contribution at all three stages: for many living in poverty it is the only place to find books for recreational reading or specialized interest reading, with the librarian serving as the guide on how to locate information as well as supplier of compelling reading. The expertise of certified librarians is pivotal for compelling reading in a foreign language, such as EFL worldwide and ELLs in the US, as well as compelling reading in children's heritage languages.